Microscopic-Based Trend in Imported Malaria among Workers of Trenggalek District Returning from Kalimantan Island, Indonesia During 2012 – 2016 - Heny Arwati; Kusmartisnawati Kusmartisnawati; Subagyo Yotopranoto; Poppy Hidayat; Yoes Prijatna Dachlan (Journal of Tropical Life Science, 2019)
Malaria in Indonesia remains a significant health problem. Trenggalek District is one of the receptive malaria areas in East Java Province, Indonesia, with mainly imported malaria from outside Java Island. The people of this district accustomed to traveling to outside Java where malaria is endemic for temporary working purposes. Usually, they have acquired malaria infection in the areas where they worked and brought to their homeland during their return to the district. The number of imported malaria cases depend on the returning season of the workers. When no workers return from outside Java malaria case is zero. During the year of 2012-2016 microscopic examination of Microscopic examination of Giemsa-stained thick blood films of the workers have been done in the working activity of Pandean Primary Health Center on their arrival from Kalimantan Island either by active or passive case detection. Microscopically positive data were reported herein to describe the trend of imported malaria in the studied areas. A total number of malaria-infected workers were 118 cases. The trend towards increasing case number yearly between 2012 and 2013 being 1.35%, then decreasing between 2013 and 2016 to only 4 cases in 2016. Different patterns of imported malaria by month were seen in each year but no specific pattern throughout the year. The Plasmodium vivax infection was predominant every year and followed by Plasmodium falciparum and mixed infection of those two species. Trends of imported malaria cases in Trenggalek district were decreased and increased irregularly in each month yearly. However, the number of cases declined annually during 2013 – 2016. Antimalarial prophylaxis and insecticides prevent the workers from malaria infection.